Analisis Strategi Pemasaran Kopi Robusta di Lampung Barat dalam Meningkatkan Daya Saing di Pasar Lokal dan Ekspor - Helpa Khadizah; Erlin Kurniati (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
This study aims to analyze robusta coffee marketing strategies implemented by business actors in West Lampung Regency in order to increase product competitiveness in local and export markets. The research method used is a qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation studies of coffee farmers, MSME players, cooperatives, and related government agencies. The results showed that the dominant marketing strategies include improving product quality, establishing local brands, utilizing social media as a means of promotion, and partnerships with cooperatives and exporters. However, there are constraints in terms of quality standardization, limited access to global markets, and weak capacity for self-promotion. Therefore, policy interventions are needed in the form of strengthening farmer institutions, facilitating product certification, digital marketing training, and support in developing product innovation. This study recommends an integrated strategy between the local government, business actors, and other stakeholders to strengthen the position of West Lampung robusta coffee as a leading commodity that is competitive in domestic and international markets.